Economic openness, power, and conflict - Blagden, DW (2012)
Economic integration between major powers has long been viewed as a force for international stability. The intuitive logic is appealing: states that are trading with and investing in each other stand to lose if that commerce is jeopardized by conflict. Yet there are sound reasons for supposing that such deepening economic integration can also shift the balance of power between major states, by causing follower economies – states that are not among the most developed in the international system – to grow faster than leading economies, and economic size and development are what underpin national material capabilities. Moreover, a rich body of theory and history suggests that such shifts in the balance of power make interstate war more likely. This dissertation argues, therefore, that economic integration can actually be a potent cause of security competition and war. A theoretical framework that unites economic theory on the differential growth impact of trade, financial flows, and technology diffusion with realist arguments on the conflict implications of polarity shifts and dynamic power differentials is constructed. It is then explored using evidence from three key historical cases: the rise of the Dutch Republic during the 1581-1648 period, the relative decline of the United Kingdom and the relative rise of other great powers between 1870 and 1914, and the differential growth rates and corresponding tensions of 1945-89. Certain scope conditions and qualifications notwithstanding, the empirical evidence supports the theoretical framework. As such, the argument that deepening economic integration raises the mutual cost of fighting and thereby makes conflict less likely is not directly refuted, but an important countervailing mechanism is found to be at work. Such a finding has implications for debates over the security implications of economic globalization, the foundations of realist theory, and the causes and potential consequences of the rise of new powers today.